Evaluation Of Anxiety In Patients Undergoing Complete Denture Treatment At Two Tertiary Care Hospitals In Rawalpindi And Islamabad - Chaudhary, Muhammad Amir Ghafoor; Khalid, Misbah; Adnan, Romeysah; Uzair, Saba; Khan, Raza Ullah; Kamran, Muhammad Farooq (Journal of Rawalpindi Medical College, 2024)
Objective: The objective of the article is to assess anxiety in patients undergoing complete denture treatment. Method: A valid pre-structured questionnaire was presented to the patients desirous of receiving complete dentures after obtaining informed consent. The questionnaire for the survey was filled out and collected from 500 patients receiving complete denture treatment. Results: Of the 500 patients, 61.1% had prior denture experience, and 38.1% were undergoing denture placement for the first time. While 84.4% felt comfortable with the idea of complete dentures, 15.4% found it repulsive. Reasons inducing anxiety in a dental setting, include materials (28.3%), instruments (8.2%), the dentist’s chair (28%), and other reasons (60.5%). Specific concerns related to complete denture use included fear of breakage (16.6%), ill-fitting prosthesis (43.3%), and discomfort with wearing and removing dentures (25%). Patients overwhelmingly appreciated having the entire procedure described beforehand (99.2%) and considered language understanding by the doctor as crucial for good treatment (97.8%). Conclusion: There is a greater need for the patient’s expectations to be understood and their doubts, concerns and fears to be narrowed by effective communication. A good understanding of patients’ mental attitudes will help us improve the technique of dentists towards complete denture treatment in a more patient-friendly way. Keywords: Anxiety, attitude, communication, complete dentures.